2010
DOI: 10.1590/s0103-84782010005000025
|View full text |Cite
|
Sign up to set email alerts
|

Produção, florescimento e frutificação de tangerineira 'Poncã' submetida à aplicação de ácido giberélico

Abstract: Produção, florescimento e frutificação de tangerineira 'Poncã' submetida à aplicação de ácido giberélico.Ciência Rural, v.40, n.3, mar, 2010. Ciência Rural, Santa Maria, v.40, n.3, p.507-512, mar, 2010 ISSN 0103-8478 Emanuel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
(19 reference statements)
2
4
0
3
Order By: Relevance
“…At every 1 mg.L -1 of bioregulator added to the spray volume, there was a reduction of 1.64 fruits per planta -1 in abscission. This phenomenon occurred due to the effect that the GA 3 has on the flowering, which is in agreement with the results of Maia et al (2010) in a study conducted with Ponkã tangerine trees (Citrus reticulata Blanco). The authors stated that the regulator reduces excessive flowering and may reduce the effect of production alternance, generating higher productivity, over the years of the tangerine trees.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…At every 1 mg.L -1 of bioregulator added to the spray volume, there was a reduction of 1.64 fruits per planta -1 in abscission. This phenomenon occurred due to the effect that the GA 3 has on the flowering, which is in agreement with the results of Maia et al (2010) in a study conducted with Ponkã tangerine trees (Citrus reticulata Blanco). The authors stated that the regulator reduces excessive flowering and may reduce the effect of production alternance, generating higher productivity, over the years of the tangerine trees.…”
Section: Resultssupporting
confidence: 91%
“…The Thus, this result is corroborating with earlier studies that indicated that the inhibitory effect of GA 3 on the flower differentiation, preventing, or decreasing the production of flowers (Maia et al, 2010). With the application of GA 3 , the plant decreased the intake of assimilates involved in flowering (Serciloto et al, 2003), increasing the supply of carbohydrates to the fruits (Pereira et al, 2011).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Esses resultados são similares aos observados em outras pesquisas com citros, as quais não verificaram alteração nas características vegetativas das plantas em concentrações que variaram de 20 a 75mg L -1 (LEONEL & RODRIGUES, 1996;SANCHES et al, 2001;SERCILOTO et al, 2003;MAIA, et al, 2010), demonstrando que a ausência de resposta possivelmente não seja devido a doses usadas. Segundo POWELL (1987), para obtenção de aumento no tamanho das plantas, há necessidade de aplicações constantes de AG 3 para a maioria das espécies, já que uma única aplicação nem sempre é suficiente para obtenção de bons resultados.…”
Section: Resultsunclassified
“…O tipo e a intensidade dessas respostas são dependentes da concentração aplicada, do estádio fenológico em que a planta se encontra no momento da aplicação e da variedade (KOSHITA et al, 1999;GRAVINA, 2007 ). Aplicações no período de indução floral geralmente reduzem o florescimento (KOSHITA et al, 1999;MAIA et al, 2010) e, durante a floração e queda das pétalas, promovem ou não a fixação de frutos. Se promoverem, há forte tendência em redução do tamanho final do fruto devido à concorrência por carboidratos (GRAVINA, 2007).…”
Section: Introductionunclassified